2006
DOI: 10.1073/pnas.0606156103
|View full text |Cite
|
Sign up to set email alerts
|

Structure of an RNA switch that enforces stringent retroviral genomic RNA dimerization

Abstract: Retroviruses selectively package two copies of their RNA genomes in the context of a large excess of nongenomic RNA. Specific packaging of genomic RNA is achieved, in part, by recognizing RNAs that form a poorly understood dimeric structure at their 5 ends. We identify, quantify the stability of, and use extensive experimental constraints to calculate a 3D model for a tertiary structure domain that mediates specific interactions between RNA genomes in a gamma retrovirus. In an initial interaction, two stem-loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 35 publications
2
53
0
Order By: Relevance
“…Prior work has shown that the MiDAS RNA dimer contains true long-range tertiary interactions involving PAL1, PAL2, and SL1-SL2 (38,45). Thus, the simplest element in the packaging signal involves both the primary sequence and the tertiary architecture of the RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has shown that the MiDAS RNA dimer contains true long-range tertiary interactions involving PAL1, PAL2, and SL1-SL2 (38,45). Thus, the simplest element in the packaging signal involves both the primary sequence and the tertiary architecture of the RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratories are developing accurate and efficient methods for modeling complex RNA structures (Badorrek et al 2006;Ding et al 2008a;Sharma et al 2008;Deigan et al 2009;Gherghe et al 2009;Lavender et al 2010). Many other laboratories are also making innovative contributions to the RNA modeling field (Massire and Westhof 1998;Tan et al 2006;Das and Baker 2007;Das et al 2008;Parisien and Major 2008;Yu et al 2008;Jonikas et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Such RNA conformational switches have been elucidated upon dimerization of HIV-1 and MLV RNAs. 11,12,19,[93][94][95][96][97][98][99] However, direct insights into RNA structure-function relationship are needed to validate this hypothesis. Another possibility is that the interaction between the gRNA and Gag, or between the gRNA and a-yet-to-be-identified cellular factor, could modulate the dual targeting of the genome.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%